Isolation, characterization and phylogenetic analysis of the resistance gene analogues (RGAs)in banana (Musa spp.) - Pei, X.; Li, S.; Jiang, Y.; Zhang, Y.; Wang, Z.; Jia, S.
According to the conservative regions of the nucleotide-binding site and the leucine-rich repeat (NBS-LRR)in resistance genes (R genes), the polymerase chain reaction (PCR)with degenerate primers was employed to isolate R gene analogues (RGAs)from five species of banana (Musa spp.), i.e. wild species of Gongjiao (AA)and Xinyiyejiao (BB), cultivated species of Zhongshandajiao (ABB), Fenjiao (AAB)and Williams (AAA), respectively. As a result, a total of 91 sequences with uninterrupted open reading frame (ORFs)were typical of RGAs out of 208 clones sequenced, of which 33 sequences with identity of deduced amino acid sequence below 97
Keywords: NBS-LRR; BANANA; DISEASE RESISTANCE GENES; DIVERSITY